A flexible z-Tree implementation of the Social Value Orientation Slider Measure (Murphy et al. 2011): Manual - Paolo Crosetto; Ori Weisel; Fabian Winter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
This manual describes a z-Tree (Fischbacher, 2007) implementation of the paper-based Social Vaule Orientation (SVO) Slider Measure by Murphy et al. (2011). Using the paper-based version instead of the slider-based version (as implemented on the SVO-Website) avoids server-traffic related delays we experienced in the latter implementation.
Keywords: C91; D03; D64; 330; z-Tree; Social Value Orientation